School Leaders as Promoters of Inclusive Digital Learning (Interdisciplinary Research in Teaching and Learning: New Perspectives and Approaches, 2024)
Technological changes, development of key competences identified by the EU and OECD as crucial for citizens, together with the consequences of the Covid-19 pandemic, can be faced only through an ecological approach rooted in pedagogical leadership. The Covid-19 pandemic has generally boosted teachers’ digital awareness and competence but there seems to be a lack of reflective practices on how digital technology can improve inclusive learning. School leaders are essential in involving and supporting the school community in the use of digital technology for inclusive learning. The Erasmus+ project ePRI4ALL has the aim to shape the digital pedagogical leadership attitudes. The partnership conducted ninety-nine in-depth semi-structured interviews with school leaders and experts in Spain, Greece, Italy and Poland. The thematic analysis highlighted challenges faced, resources available and professional development needs and grounded the learning materials developed (modules, MOOC and online app). This article will present the results for the 25 Italian interviews analyzing the role of digital education in school, the training needs of school leaders and the main challenges that they have to face in order to be promoters of an inclusive and digitally competent school.